Learn Docker in a Month of Lunches video edition - Stoneman, Elton; Stoneman, Elton (Manning Publications, 2020)
This book took me from someone interested in Docker to someone using it effectively in several projects. Mark Elston, Advantest America Go from zero to production readiness with Docker in 22 bite-sized lessons! Learn Docker in a Month of Lunches is an accessible task-focused guide to Docker on Linux, Windows, or Mac systems. In it, you'll learn practical Docker skills to help you tackle the challenges of modern IT, from cloud migration and microservices to handling legacy systems. There's no excessive theory or niche-use cases--just a quick-and-easy guide to the essentials of Docker you'll use every day. about the technology The idea behind Docker is simple: package applications in lightweight virtual containers that can be easily installed. The results of this simple idea are huge! Docker makes it possible to manage applications without creating custom infrastructures. Free, open source, and battle-tested, Docker has quickly become must-know technology for developers and administrators. about the book Learn Docker in a Month of Lunches introduces Docker concepts through a series of brief hands-on lessons. Following a learning path perfected by author Elton Stoneman, you'll run containers by chapter 2 and package applications by chapter 3. Each lesson teaches a practical skill you can practice on Windows, macOS, and Linux systems. By the end of the month you'll know how to containerize and run any kind of application with Docker. what's inside Package applications to run in containers Put containers into production Build optimized Docker images Run containerized apps at scale about the audience For IT professionals. No previous Docker experience required. about the author Elton Stoneman is a consultant, a former architect at Docker, a Microsoft MVP, and a Pluralsight author. A well-written and cogent approach to learning and implementing containerized applications with Docker. Philip Taffet, SOHOsoft This is a must-have resource for anyone wanting to come to grips with Docker--from novice to expert, there's something for everyone. Kevin Orr, Sumus Solutions I recommend anyone serious about learning Docker begin with this book. Marcus Brown, Tradewind Energy NARRATED BY JULIE BRIERLEY.